Tetrahydrocarbazoles are a novel class of potent P-type ATPase inhibitors with antifungal activity - Bublitz, M; Kjellerup, L; O'Hanlon Cohrt, K; Gordon, S; Mortensen, AL; Clausen, JD; Pallin, TD; Hansen, JB; Fuglsang, AT; Dalby-Brown, W; Winther, A-ML (Public Library of Science, 2018)
We have identified a series of tetrahydrocarbazoles as novel P-type ATPase inhibitors. Using a set of rationally designed analogues, we have analyzed their structure-activity relationship using functional assays, crystallographic data and computational modeling. We found that tetrahydrocarbazoles inhibit adenosine triphosphate (ATP) hydrolysis of the fungal H+-ATPase, depolarize the fungal plasma membrane and exhibit broad-spectrum antifungal activity. Comparative inhibition studies indicate that many tetrahydrocarbazoles also inhibit the mammalian Ca2+-ATPase (SERCA) and Na+,K+-ATPase with an even higher potency than Pma1. We have located the binding site for this compound class by crystallographic structure determination of a SERCA-tetrahydrocarbazole complex to 3.0 Å resolution, finding that the compound binds to a region above the ion inlet channel of the ATPase. A homology model of the Candida albicans H+-ATPase based on this crystal structure, indicates that the compounds could bind to the same pocket and identifies pocket extensions that could be exploited for selectivity enhancement. The results of this study will aid further optimization towards selective H+-ATPase inhibitors as a new class of antifungal agents.